A short psychometric scale to evaluate the cognitive status of aged Spanish speakers - Sánchez-Ayéndez, Melba; Cabán, Carlos A; Fernández, Leticia; Rosich, Walter; Dávila, Ana L; Larriuz, María Celeste; Hernández, Johan; García Guruxarri, Alberto; Palloni, Alberto (Puerto Rico health sciences journal, 2003)
During the last ten years there has been an interest for determining the prevalence and incidence of dementia among older adults and for cognitive tests that do to discriminate by level of education. This article revolves around the validation of a minimental exam, the Cabán minimental, to measure the cognitive capacity of Spanish-speaking adults 60 years of age and older; a test that is not affected by level of education. The factors measured in the Cabán minimental are: orientation, visual and motor coordination, learning, recent memory and abstraction. The validation process underwent two phases. During the first one, the Cabán test was subjected to construct validation and internal and predictive consistency tests. The second stage comprised a comparison between the Cabán and Folstein minimentals. The Cabán showed a statistically significant difference to discriminate for subjects with dementia. Results also suggest that the Cabán is not as much affected as the Folstein by differences in education.